High-resolution records of growth temperature and life history of two Nacella limpet species, Tierra del Fuego, Argentina - Nicastro, Adam.; Surge, Donna.; Briz Godino, Ivan; Alvarez, Myrian Rosa; Schöne, Bernard ,R.; Bas, Maria (Palaeogeography, Palaeoclimatology, Palaeoecology)
Stable isotope ratios in patelloid limpets of the genus Patella have been established as proxies for coastal environmental change at sub-monthly resolution along the eastern North Atlantic and Mediterranean Sea. Nacella deaurata (Gmelin, 1791) and N. magellanica (Gmelin, 1791) are common intertidal species of patelloid limpets inhabiting the coast of Tierra del Fuego, Argentina/Chile and are commonly found in Holocene archaeological deposits. Here, we examine oxygen and carbon isotope ratios (δ18Oshell and δ13Cshell, respectively) of modern specimens of N. deaurata and N. magellanica to test the hypotheses that: 1) they form their shells in isotopic equilibrium with ambient water; and 2) prominent growth lines form annually. Based on growth margin analysis of δ18Oshell values, we identified a positive offset of 1.3±0.4? (N. deaurata) and 1.3±0.3? (N. magellanica) from expected equilibrium, similar to other patelloid limpets. Because the offset is relatively consistent between observed and expected values, it can be taken into account to reliably reconstruct growth temperature. Seawater temperature estimated from oxygen isotope time series data falls within the observed range. Thus, N. deaurata and N. magellenica shells serve as reliable proxy archives of seasonal variation in coastal seawater temperature. Time series of δ13C shell values do not vary seasonally in all shells; hence, the influence on its variation requires further study. The timing of prominent growth lines contextualized by the δ18Oshell time series form twice a year and therefore cannot be used to estimate lifespan. Future isotopic analysis of archaeological Nacella shells can potentially provide much needed information about Holocene climate change at sub-monthly resolution from high-latitude South American locations, and contribute to our understanding of human behavior and human-climate interactions. Fil: Nicastro, Adam. University Of North Carolina At Chapel Hill; Estados Unidos Fil: Surge, Donna. University Of North Carolina At Chapel ...